2017
DOI: 10.21037/gs.2016.08.03
|View full text |Cite
|
Sign up to set email alerts
|

Are breast cancer stem cells the key to resolving clinical issues in breast cancer therapy?

Abstract: Despite the dramatic advances in breast cancer treatment over the past two decades, it is still the most common malignancies in women. One of the reasons patients succumb to breast cancer is treatment resistance leading to metastasis and recurrence. Recently, cancer stem cells (CSCs) have been suggested as a cause of metastasis and recurrence in several cancers because of their unique characteristics, including self-renewal, pluripotency, and high proliferative ability. Increasing evidence has implicated breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
0
40
0
3
Order By: Relevance
“…Chemoresistance is a characteristic of CSCs [ 31 , 38 , 39 ]. Recent studies from our laboratory showed that inhibition of WAVE3 expression sensitized MDA-MB-231 and BT549 cells to chemotherapy [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemoresistance is a characteristic of CSCs [ 31 , 38 , 39 ]. Recent studies from our laboratory showed that inhibition of WAVE3 expression sensitized MDA-MB-231 and BT549 cells to chemotherapy [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, there are several established markers of breast CSCs. The phenotype of CD44 + /CD24 -/low and overexpression of ALDH1, EpCAM, and nestin suggest a worsened prognosis of BC in women [74]. CD24, CD44, EpCAM, and ALDH1 have been shown to be good markers of CSCs also in chemically induced mammary carcinogenesis in rats [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of metabolomics for investigating several cancers has also been reported not only for early diagnosis, but also for the selection of therapeutic agents for patients with advanced cancer . Metabolomics contributes to the treatment response of breast cancer by interpreting molecular measures using specific computational models . In colorectal cancer, a number of groups have characterized metabolomic features using various analytical platforms .…”
Section: Discussionmentioning
confidence: 99%